Pengembangan Media Permainan Ajian Jaran Goyang Untuk Meningkatkan Efikasi Diri Siswa SMP - Ayuningtyas, Putri; Nawantara, Rosalia Dewi; Setyaputri, Nora Yuniar (Universitas Nusantara PGRI Kediri, 2022)
The current field phenomenon says that some junior high school-age children in the Grogol Kediri area are less able to choose something suitable for themselves because they do not understand the importance of self-efficacy. Therefore, the role of the guidance and counseling teacher is very important in today's conditions to provide service through the media. The media can use the favorite traditional arts of Kediri teenagers, namely Jaranan art. This media can be called the game media